MOLECULAR, 13C, AND 14C EVIDENCE FOR THE ALLOCHTHONOUS AND ANCIENT ORIGIN OF C16-C18 N-ALKANES IN MODERN SOILS - Lichtfouse E.; Bardoux G.; Mariotti A.; Balesdent J.; Ballentine D.C.; Macko S.A. (My University, 1997)
The heterogeneous isotopic composition of C3 and C4 plants can be used to follow the fate of plant carbon into soil organic molecules. Thus, after 23 years of maize cropping (C4) on a soil which was previously under C3 vegetation, C25-C33 soil n-alkanes are 13C-enriched up to 9%% relatively to the initial C3 soil, reflecting the input of 13C-enriched n-alkanes from maize waxes. In sharp contrast, C16-C18 soil n-alkanes do not show any significant 13C/12C variation over the same time interval. This absence of isotopic variation, along with consideration of their relative concentration, absolute concentration, and biodegradability, demonstrate that these substances must represent a regular input from an external source. Evidence of a large contribution of an ancient source, amounting to more than 65% of the alkane fraction, is given by a 14C-age of 8510 yrs bp. Moreover, short-chain n-alkanes from soils, diesel fuel, diesel automobile exhaust, and petroleum products exhibit similar distributions and δ13C values. These findings suggests that C16-C18 soil n-alkanes represent a non-point source pollution of ancient hydrocarbons either carried by aerosols or entering the soil via continuous hydrocarbon seepage from the deep sedimentary rocks of the Paris basin.